Computational fluid dynamics study of air pollutant dispersion around Kuantan - Norliyana, Erain (2019)
Air pollutant like the chlorine is harmful to living things, environment and building structures when it accumulates in the air in sufficiently high concentration. Exposure to chlorine gas can cause acute or chronic effects depending on its concentration. In Malaysia, Gebeng industrial area is one of the largest industrial area that consists of various processing plant such as petrochemical and polymer plant where the chlorine is commonly used in the petrochemical and polymer plants such as Polyplastics Asia Pacific, Lynas, Petronas-MTBE and Kaneka Malaysia. So, there are high potential to accidental release of chlorine in the selected area thus as the main reason on choosing the chlorine as pollutant. Air pollutant dispersion is significantly affected by the meteorological and topographical conditions. The field experiment measurement has the limitations to provide detail information of air flow on complex terrain and hence computational fluid dynamics (CFD) techniques is applied to provide the comprehensive information on the species transport and turbulence simultaneously. To ensure the accuracy of the air flow on CFD model, it must be validated before it routinely used. So, one of the objectives for this study is to model the wind flows past a scaled-down model using particle image velocimetry (PIV) measurement and compare with the CFD simulation. To achieve this objective, parameter such as wind speeds and directions was collected and will be used to obtain the results by using CFD as a simulation tools. The typical eastern wind with wind speed 1.78 m/s is used. The turbulence flow was modelled using scale-adaptive simulation (SAS) turbulence model. The model was validated with the PIV measurement on the scale down topography model. The CFD prediction showed good agreement with the error ranging 1.5 to 2.6% from the PIV measurement. Hence, the model can be used to evaluate the combine effect of surface terrain, wind direction and speed on the pollution dispersion around Gebeng industrial area. It was found that the residential area R1 (Kampung Baru Gebeng, Tanjung Rhu, Kampung Sungai Ular, Kampung Darat Sungai Ular and Kampung Baging) and R2 (Kampung Selamat, Kampung Berahi, Kampung Balok, Kampung Seberang Balok Kampung Balok Baru and Kampung Balok Perdana) are affected when the chlorine leakage occurs during June to September and November to January, respectively. Accidental release of this chlorine gas may have led to the emergencies. Hence, it is also important to develop a suitable safety evacuation plan in the event accidental chlorine leak. Suitable safety evacuation route and points is proposed for the case when the residential area R1 and R2 are affected.